The hospice in Valognes, France - Auteur inconnu (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: The hospice in Valognes, France. The hospice with its church in Valognes, France Iconographic Collections Keywords: Postcard | France | Hospitals | French | Church
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église